Green sukuk and carbon neutrality in Malaysia: an analysis of the effectiveness of Islamic finance in funding renewable energy projects - Mohd Thas Thaker, Hassanudin; Lechumanan, Bawani; Syed Salleh, Sharifah Nabilah (World Scientific, 2026)
This chapter examines the role of green sukuk in advancing carbon neutrality in Malaysia, focusing on their effectiveness in funding renewable energy projects. Green sukuk are Shariah-compliant financial instruments that merge Islamic finance principles with environmental sustainability goals. Malaysia, a global leader in Islamic finance, issued the world’s first green Sukuk (singular form of sukuk) in 2017, setting a precedent for sustainable finance. The study explores the operational mechanisms and market dynamics of green sukuk and highlights successful case studies such as Tadau Energy and Quantum Solar Park. These projects demonstrate the potential of green sukuk to attract diverse investors and support large-scale renewable energy initiatives. The chapter also addresses challenges in the adoption and implementation of green sukuk, including high initial costs, regulatory complexities, and market awareness. Through qualitative research and expert interviews, the study provides insights into the socioeconomic and environmental impacts of green sukuk, emphasizing their role in promoting sustainable development and financial inclusion. The findings suggest that while green sukuk have significantly contributed to Malaysia’s renewable energy sector, further efforts are needed to enhance financial support market and innovation in green finance products. This research underscores the importance of integrating Islamic finance with sustainability objectives to achieve carbon neutrality and foster a resilient, inclusive economy.